Quality of life after quitting smoking and initiating aerobic exercise. Issue 9 (21st October 2017) - Bloom, Erika Litvin; Minami, Haruka; Brown, Richard A.; Strong, David R.; Riebe, Deborah; Abrantes, Ana M.
Abstract: Quitting smoking and aerobic exercise each improve health. Although smokers may be concerned that quitting smoking will reduce their quality of life (QOL), recent research has shown that cessation is associated with QOL benefits. Elements of smoking cessation interventions, such as exercise, may contribute to changes in QOL. However, it is unknown whether initiating exercise in the context of smoking cessation is associated with greater or different effects on QOL than smoking cessation alone. The current study is a secondary analysis of data from a randomized trial ( n  = 61) of an exercise intervention for smoking cessation. We hypothesized that smoking abstinence and engagement in exercise would have positive, additive effects on QOL at end-of-treatment, 6- and, 12-month follow-ups. Sedentary adult smokers were randomized to the exercise intervention or a health education control (HEC) group. Additionally, all participants received smoking cessation counseling and nicotine patches. Data were analyzed using actual engagement in exercise, rather than group assignment as a proxy for exercise engagement, because some HEC participants also began exercising. Abstinence was positively associated with higher total and physical health QOL at follow-up. Exercise was not associated with total QOL and only marginally associated with physical health QOL, but was positively related to overall sense of well-being. Emphasizing that smoking cessation is associated with higher QOL may help motivate smokers to initiate quit attempts.